Determining a resilient stope boundary for underground mass mining projects (Rudarsko-geološko-naftni zbornik, 2022)
Uncertainty-based stope boundary optimization is a complex part of underground mine planning, especially in mass mining projects and notably block caving. Besides, grade variation and grade uncertainty are significant sources of error in mining projects. This paper presents a procedure to determine a resilient block-cave stope boundary considering the ore grade uncertainties. The procedure applies the floating stope algorithm, the maximum upside/minimum downside, and the value at risk for design evaluation. The floating stope algorithm is customized for block caving and is used to determine the stope boundary over some simulated grade models. The idea fits into a multi-criteria decision-making problem. Finally, the most resilient stope boundary is selected by considering several criteria and the TOPSIS method. According to the results, the resilient stope boundary covers an area where the mineable reserve is 977 Mt with an average copper grade of 0.51%.